Thule Eskimo culture : an anthropological retrospective - McCartney, Allen P. (Paper (Archaeological Survey of Canada) ;, 1979)
Proceedings of a symposium devoted to Thule archaeology and related northern studies held at the 10th annual meeting of the Canadian Archaeological Association in Ottawa during May, 1977. Papers address Thule chronology and cultural history, prehistoric-recent continuities, adaptation and climatological relationships, site interpretations, technology and art, human biology, and archaeological development. Focusses on last thousand years of Neo-Eskimo cultural evolution in Alaska, Canada, and Greenland.